2019
DOI: 10.1136/jech-2018-211350
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and bystander behaviour and health outcomes among adolescents in Ireland

Abstract: BackgroundLittle is known about the impact of being a bystander to bullying. This study compared health outcomes among bullies, victims and bystanders, and investigated actions taken by bystanders when they saw bullying.MethodParticipants included 7522 students aged 12–18 years that completed self-report questionnaires in the 2013/2014 Health Behaviour in School-aged Children survey. Binary logistic regression models (controlled for bully, victim, bystander status and demographic variables) were used to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 30 publications
2
34
1
Order By: Relevance
“…The answer categories were ‘haven’t’, ‘once or twice’, ‘2 or 3 times a month’, ‘about once a week’, and ‘several times a week’. Responses were dichotomised into 0 = never, and 1 = at least once (as in [20, 26]). Fighting was measured by asking ‘During the past 12 months, how many times were you in a physical fight?’, with the following response categories: ‘I have not been’, ‘1 time’, ‘2 times’, ‘3 times’, ‘4 times or more’.…”
Section: Methodsmentioning
confidence: 99%
“…The answer categories were ‘haven’t’, ‘once or twice’, ‘2 or 3 times a month’, ‘about once a week’, and ‘several times a week’. Responses were dichotomised into 0 = never, and 1 = at least once (as in [20, 26]). Fighting was measured by asking ‘During the past 12 months, how many times were you in a physical fight?’, with the following response categories: ‘I have not been’, ‘1 time’, ‘2 times’, ‘3 times’, ‘4 times or more’.…”
Section: Methodsmentioning
confidence: 99%
“…According to the social-ecological diathesis stress model of bullying (Swearer & Hymel, 2015 ), involvement in bullying is a negative life event that may contribute to psychopathology (e.g., internalizing and externalizing problems), depending on an individual’s personal characteristics, life experiences, and the quality of their social environments. Indeed, there is growing evidence that simply witnessing bullying is associated with increased psychological distress among bystanders (e.g., Callaghan, et al, 2019 ; Janosz et al, 2008 ; Lambe et al, 2017 ; Rivers et al, 2009 ). However, it is not yet clear whether youth who actually stand up for victims experience poorer mental health outcomes.…”
Section: Defending and Internalizing Symptomsmentioning
confidence: 99%
“…For example, compared to passive bystanders, youth who defend are more likely to report experiencing negative emotions like guilt (Mazzone et al, 2016 ; Pronk et al, 2016 ) and anger (Lambe et al, 2017 ; Trach & Hymel, 2019 ) while witnessing bullying. Similarly, after controlling for demographic characteristics and previous involvement as a bully or victim, bystanders who reported helping a victim of bullying in the past 2–3 months also reported experiencing elevated psychological symptoms, whereas doing nothing in response to witnessed bullying was not associated with any mental health symptoms (Callaghan et al, 2019 ). Self-reported defending has also been positively associated with concurrently measured internalizing symptoms (Evans et al, 2019 ; Jenkins et al, 2017 ; Jenkins & Frederick, 2017 ; Wu et al, 2016 ).…”
Section: Defending and Internalizing Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like self-concept, wellbeing has been also negatively associated with victimization in adolescence (Callaghan et al, 2015;Weng et al, 2017;Gini et al, 2018;Cañas et al, 2020). Additionally, some works have indicated that victimization has a negative influence on the victims' wellbeing (Låftman and Modin, 2017;Callaghan et al, 2019), so it is not surprising that bullying victims are significantly more likely to experience low life satisfaction. For this reason, some investigations into youth violence have considered victimization as a salient risk factor for poor life satisfaction in adolescence (Méndez-Giménez et al, 2017;Gini et al, 2018).…”
Section: Relationship Between Victimization and Emotional Adjustmentmentioning
confidence: 99%